2011
DOI: 10.1111/j.1530-0277.2011.01594.x
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Brainstem Response (ABR) Abnormalities Across the Life Span of Rats Prenatally Exposed to Alcohol

Abstract: Background Fetal Alcohol Syndrome is a leading cause of neurodevelopmental impairments (NDI) in developed countries. Sensory deficits can play a major role in NDI, yet few studies have investigated the effects of prenatal alcohol exposure on sensory function. In addition, there is a paucity of information on the life-long effects of prenatal alcohol exposure. Thus, we sought to investigate the effects of prenatal alcohol exposure on auditory function across the life span in an animal model. Based on prior find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 66 publications
(137 reference statements)
15
36
0
Order By: Relevance
“…Binaural ‘open field’ tone pips in the ascending order of 2, 4, 8, 16 and 32 kHz were delivered through either a headphone (TDH-39P, Telephonics Corporation, Farmingdale, NY) for the 2–8 kHz tone pips or a tweeter speaker (Super Tweeter, Tandy Corporation, Fort Worth, TX) for the 16 and 32 kHz tone pips that were placed in front of the animal (rise/fall time = 0.5 ms, plateau = 10 ms, polarity = alternating, repetition rate = 19/s). These tone pip frequencies cover the range of greatest hearing sensitivity for a rat and are comparable to the range tested in other recent rat ABR or mouse auditory neurophysiology studies, permitting an assessment of frequency-dependent effects (Chen & Henderson, 2009; Church et al, 2004; Church et al, 2012; Henry, 2003; Tanaka et al, 2003). …”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…Binaural ‘open field’ tone pips in the ascending order of 2, 4, 8, 16 and 32 kHz were delivered through either a headphone (TDH-39P, Telephonics Corporation, Farmingdale, NY) for the 2–8 kHz tone pips or a tweeter speaker (Super Tweeter, Tandy Corporation, Fort Worth, TX) for the 16 and 32 kHz tone pips that were placed in front of the animal (rise/fall time = 0.5 ms, plateau = 10 ms, polarity = alternating, repetition rate = 19/s). These tone pip frequencies cover the range of greatest hearing sensitivity for a rat and are comparable to the range tested in other recent rat ABR or mouse auditory neurophysiology studies, permitting an assessment of frequency-dependent effects (Chen & Henderson, 2009; Church et al, 2004; Church et al, 2012; Henry, 2003; Tanaka et al, 2003). …”
Section: Methodsmentioning
confidence: 78%
“…Presenting stimuli at fast repetition rates constitutes an auditory stressor test that can reveal neurological abnormalities (e.g., poor neural synchrony) that may not be present when stimuli are presented at a slow repetition rate (Church et al, 2012; Santos et al, 2004; Starr et al, 2001). Thus, Experiment #2 used this stressor test to see if MDMA treatment interacted with the stimulus repetition rate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study exemplifies an important feature of alcohol exposure during pregnancy, that is in addition to impacting the mother and fetus, the fetal germline is vulnerable. Neurobiological : Rats were administered alcohol (6 mg/kg) and were assessed for auditory brain stem response at 22 days, 7 months, and 17 months after birth; in accordance with the Barker hypothesis, the authors reported developmental delay that dissipated at 7 months, and enhanced deficits at 17 months, thus recommending long-term follow up of prenatally alcohol-exposed kids (Church et al, 2012). Nutrient homeostasis : Alcohol-exposed rats were studied up to 14 months after birth, and male rats specifically demonstrated significantly higher fasting serum triglyceride levels.…”
Section: Prenatal Alcohol-induced Adult Onset Diseasesmentioning
confidence: 95%
“…Foetal alcohol syndrome is characterised by congenital malformations associated with impaired hearing. There are four types of auditory disorders found in FAS, namely: delay in the development of auditory maturation, sensory hearing loss -teratogenic effect of alcohol on the auditory system causes damage to the inner ear cells in the embryo [11], hearing loss caused by recurrent serious otitis of the middle ear, and central hearing loss [12].…”
Section: Therapeutic Proceduresmentioning
confidence: 99%